2010
DOI: 10.1007/s10529-010-0264-2
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of an acid phosphatase from Trichoderma harzianum

Abstract: An acid phosphatase from Trichoderma harzianum was purified in a single step using a phenyl-Sepharose chromatography column. A typical procedure showed 22-fold purification with 56% yield. The purified enzyme showed as a single band on SDS-PAGE with an apparent molecular weight of 57.8 kDa. The pH optimum was 4.8 and maximum activity was obtained at 55 degrees C. The enzyme retained 60% of its activity after incubation at 55 degrees C for 60 min. The K (m) and V (max) values for p-nitrophenyl phosphate (p-NPP)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 27 publications
0
12
0
2
Order By: Relevance
“…In this study, the ACPase from T. asperellum Q1 was purified by a combination of ammonium sulphate precipitation, ion-exchange, and gel filtration chromatography. The purified enzyme showed as a single band on SDS-PAGE and the apparent molecular weight was generally consistent with that of T. harzianum (Leitão et al 2010); however, it was obviously less than that from A. caespitosus (186 and 190 kDa) (Guimarães et al 2004) and greater than that from A. fumigatus (18 kDa) (Bernard et al 2002).…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…In this study, the ACPase from T. asperellum Q1 was purified by a combination of ammonium sulphate precipitation, ion-exchange, and gel filtration chromatography. The purified enzyme showed as a single band on SDS-PAGE and the apparent molecular weight was generally consistent with that of T. harzianum (Leitão et al 2010); however, it was obviously less than that from A. caespitosus (186 and 190 kDa) (Guimarães et al 2004) and greater than that from A. fumigatus (18 kDa) (Bernard et al 2002).…”
Section: Discussionmentioning
confidence: 78%
“…But its role in P-solubilization differs from different kinds of microorganisms. Shen et al (2011) demonstrated that most plant growth-promoting rhizo-bacteria can excrete ACPase, and some studies have also been conducted on the purification and characterization of ACPase from fungi (Shimizu 1993;Guimarães et al 2004;Leitão et al 2010). An ACPase from T. harzianum was purified in a single step using a phenyl-sepharose chromatography column.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ensaio enzimático: A atividade da fosfatase ácida foi medida de acordo com (Leitão et al, 2010), utilizando como substrato fosfato de p-nitrofenilo sal disódico hexahidratado (p-NPP) (Sigma Aldrich ™). Uma unidade (1U) de atividade da fosfatase ácida será definida como 1 μM de p-nitrofenol (p-NP) formado por minuto (Ames, 1966).…”
Section: Metodologia Analíticaunclassified
“…Entre os microrganismos solubilizantes de fosfato, as estirpes dos gêneros bacterianos Pseudomonas, Bacillus, Rhizobium e fungos tais como Aspergillus sp., Humicola sp., Mucor sp., Penicillium sp., Metarhizium sp. e Trichoderma harzianum são poderosos solubilizantes de fosfato (Guimarães et al, 2004;Boyce e Walsh, 2007;Leitão, et al 2010).…”
Section: Introductionunclassified